Magnetic Properties of Metal Clusters Coordinated with (Nitronyl Nitroxide)‐Substituted Amidinate Ligands. Issue 36 (23rd September 2020) - Tanimoto, Ryu; Suzuki, Shuichi; Kozaki, Masatoshi; Kanzaki, Yuki; Shiomi, Daisuke; Sato, Kazunobu; Takui, Takeji; Tanaka, Rika; Okada, Keiji
Abstract: We prepared dicopper, disilver, and tetragold clusters ligated with (nitronyl nitroxide)‐substituted amidinate (NN‐amidinate). NN‐substituted amidine was prepared from N, N ′‐diphenylcarbodiimide via a nucleophilic reaction with nitronyl nitroxide as a radical anion. The NN‐amidinate ligand was generated by treatment with an appropriate base, and subsequent addition of copper(I), silver(I), or gold(I) sources gave the respective metal cluster systems of Cu2 ‐(NN‐amidinate)2, Ag2 ‐(NN‐amidinate)2, or Au4 ‐(NN‐amidinate)4 . These radical‐metal clusters exhibited excellent stability, even in solution under aerated conditions, making them easy to handle. Single crystals were obtained by recrystallization from suitable solvent systems. The spin structures of the cluster systems were investigated by ESR spectroscopy and magnetic susceptibility measurements, which indicated the existence of weak intramolecular, spin‐spin interactions between the NN moieties. Abstract : Radical‐metal cluster complexes were fabricated. A (nitronyl nitroxide radical)‐substituted amidine derivative was converted to dicopper, disilver, and tetragold complexes whose structures were identified by crystal structure analyses. These complexes are quite stable in solution under aerated conditions. The ESR and magnetic susceptibility measurements revealed the existence of weak antiferromagnetic interactions between the radical moieties.